Research on two-phase grid task scheduling based on Petri nets - XIONG Zeng-gang 1; YANG Yang2; ZENG Ming2 (Tongxin xuebao)
Firstly, the grid resource management model was described which was integrated P2P mode. Then, a two-phase grid task scheduling method was proposed. What’s more, a hierarchical colored petri nets（HCPN） and colored timed petri nets were constructed. Finally, grid reachable task graph was analysed and a best grid task scheduling scheme was giren.